Penegakan Hukum bagi Anak Pelaku Tindak Pidana Kekerasan Serta Peran DP3AP2 DIY dalam Melakukan Pelindungan terhadap Korban: - - Helpia Helpia; Adlia Nur Zhafarina (Jurnal Hukum Lex Generalis, 2025)
This study discusses legal protection for victims of child violence from a positive legal perspective and the judge's considerations in Decision Number 1/Pid.Sus-Anak/2023/PN Yyk which is associated with the principle of equality before the law. The method used is a mixed normative and empirical approach, by examining laws and regulations and court decisions. The results of the study indicate that protection for victims has been accommodated in national law, while judges apply the principle of legal equality proportionally through a restorative justice approach to child perpetrators.